Persistence and Dissemination Capacities of a blaNDM-5-Harboring IncX-3 Plasmid in Escherichia coli Isolated from an Urban River in Montpellier, France - Florence Hammer-Dedet; Fabien Aujoulat; Estelle Jumas-Bilak; Patricia Licznar-Fajardo (Antibiotics, 2022)
To investigate the capacities of persistence and dissemination of blaNDM-5 within Escherichia coli and in aquatic environment, we characterized E. coli (sequence type 636) strains B26 and B28 isolated one month apart from the same urban river in Montpellier, France. The two isolates carried a pTsB26 plasmid, which sized 45,495 Kb, harbored blaNDM-5 gene and belonged to IncX-3 incompatibility group. pTsB26 was conjugative in vitro at high frequency, it was highly stable after 400 generations and it exerted no fitness cost on its host. blaNDM-5harboring plasmids are widely dispersed in E. coli all around the world, with no lineage specialization. The genomic comparison between B26 and B28 stated that the two isolates probably originated from the same clone, suggesting the persistence of pTsB26 in an E. coli host in aquatic environment.